A domain‐decomposition strategy for a compressible multi‐phase flow interacting with a structure. (14th April 2014) - Greco, M.; Colicchio, G.; Faltinsen, O.M.
SUMMARY The problem of a high‐pressure gas cavity and its interaction with surrounding liquid and a close‐by structure is examined numerically. Even though this is of interest in many practical applications, here, the focus is on an underwater explosion. A one‐way DD strategy coupling a radial and a 3D solver for compressible multiphase flows is proposed, and the different components are successfully validated. This is a time‐space DD, which assumes the explosion that occurs sufficiently far from boundaries. It means that the radial solution is used everywhere until radial symmetry is no more applicable. When acoustic waves reach a close structure, the radial solution initiates the 3D solution near the body and continues to be applied only far from the structure and to provide the boundary conditions for the 3D sub‐domain. The advantage is to limit the computational costs and preserve reliability and accuracy. The radial solution could be applied to assess local damages during the initial acoustic phase; the time‐space DD needs to be used to investigate both local and global consequences on the vessels. The structure is modeled both as a rigid wall and as an orthotropic plate, which provides a good representation of the bottom grillages of ships. Copyright © 2014 John Wiley & Sons, Ltd.